Analysis of the Relationship Perception of Benefits and Perception of Obstacles to Vaccinate COVID-19 Booster Dosage - Diyah Nur Ekowati; Nurjazuli Nurjazuli; Bagoes Widjanarko (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the relationship between perceived benefits and perceived obstacles to vaccinating booster doses of COVID-19 in Pemalang Regency. This research is quantitative research with a cross-sectional study design. From the results of the hypothesis testing, it was obtained that the p-value of perceived benefits was 0.000, and the P value of perceived obstacles was 0.000. In conclusion, there is a significant relationship between the perception of benefits and intention to vaccinate booster doses of COVID-19 and a meaningful relationship between perceptions of obstacles and choice to vaccinate booster doses of COVID-19. Keywords: Booster, Barriers, Benefits, Intentions, COVID-19 Vaccine